2021
DOI: 10.1371/journal.pone.0257541
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for unfavorable clinical outcomes in patients with brain abscess in South Korea

Abstract: Background Brain abscess can be life-threatening and manifest various neurological findings, although the mortality rate has decreased recently. We investigated the risk factors for unfavorable outcomes of patients with brain abscess. Methods A retrospective cohort study examined patients with brain abscess seen from May 2005 to December 2018 in a tertiary care hospital in Seoul, South Korea. We reviewed the medical records for clinical findings, therapeutic modalities, and prognostic factors of brain absces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Uncommonly, Lactobacillus species can be pathogenic, resulting in bacteremia, endocarditis, dental abscesses, meningitis, liver abscess, and other intra-abdominal infections [9][10][11]. There are sparse case reports where Lactobacillus species are isolated from brain tissue, with a possible odontogenic primary source, however, these reports found Lactobacillus catenaformis and not Lactobacillus fermentum, which was isolated from our patient [4][5][6].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Uncommonly, Lactobacillus species can be pathogenic, resulting in bacteremia, endocarditis, dental abscesses, meningitis, liver abscess, and other intra-abdominal infections [9][10][11]. There are sparse case reports where Lactobacillus species are isolated from brain tissue, with a possible odontogenic primary source, however, these reports found Lactobacillus catenaformis and not Lactobacillus fermentum, which was isolated from our patient [4][5][6].…”
Section: Discussionmentioning
confidence: 67%
“…It is a catalase-negative, Gram-positive rod, and facultative anaerobic bacteria that can be found as a commensal organism in the gastrointestinal tract, genitourinary tract, and the oral cavity. There are rare case reports where the pathogen is isolated from brain tissue with a possible odontogenic primary source [4][5][6]. We present a case of a middle-aged woman with uncontrolled diabetes who had Lactobacillus fermentum isolated from a left parietal lobe brain abscess in the absence of bacteremia or a clear source of infection.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported some other prognostic factors for BA. Cho et al reported that higher Sequential Organ Failure Assessment, pre-existing hemiplegia, and higher Charlson comorbidity index were associated with unfavorable clinical outcomes [ 10 ]. Widdrington et al reported that a reduced Glasgow coma scale (GCS) (OR, 16.6; 95% CI, 5.63–48.93; P < 0.001), focal neurological deficit (OR, 5.50; 95% CI, 1.67–18.08; P = 0.003), and seizures (OR, 3.68; 95% CI, 1.26–10.78; P = 0.014) at presentation were independently associated with an unfavorable clinical outcome (death or disability) [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…BAs are usually caused by bacteria, although can also be caused by other pathogens including fungi and protozoa, and sometimes polymicrobial infection should be considered [ 7 ]. The causative pathogens of bacterial BAs vary according to geographic location, age, underlying medical conditions, and mode of infection [ [8] , [9] , [10] ]. A meta-analysis of cohort studies summarised data of 9699 patients from 123 studies and showed that the most common causative microorganisms were Streptococcus (34%) and Staphylococcus species (18%) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective cohort study examined patients with brain abscesses recruited from May 2005 to December 2018 in South Korea. This study showed that risk factors for mortality were higher Sequential Organ Failure Assessment (SOFA) [OR 1.52, 95% CI (1.21–1.92)], preexisting hemiplegia [OR 7.65, 95% CI (1.85–68.92)], and a higher CCI [OR 1.28, 95% CI (1.03–1.59)] [49].…”
Section: Early Complications and Outcomesmentioning
confidence: 95%